(untitled) (International Journal of Innovative Technologies in Economy, 2025)
The development of any region can only be achieved through the mobilization of all its local resources, the concerted efforts of its stakeholders, and mutual cooperation, while establishing a unified future vision. It is essential to involve all actors in the region, without exception, in the planning and implementation of development initiatives. Additionally, aligning the objectives of all stakeholders with the general goals of the region is crucial to ensuring the success of planned development and preventing any obstruction or disruption by any involved party. Based on this premise, this study seeks to identify the role of local governance in realizing the development process and enhancing the engagement of key actors. The research explores the concept of local development and its main stakeholders, including the state and local administration, the private sector, citizens, and civil society organizations. It also examines the concept of local governance and its role in implementing local development and strengthening the contribution of local administration, the private sector, and civil society organizations.